Dislocations that Decrease Size Mismatch within the Lattice Leading to Ultrawide Band Gap, Large Second‐Order Susceptibility, and High Nonlinear Optical Performance of AgGaS2 - Zhou, Hui‐Min; Xiong, Lin; Chen, Ling; Wu, Li‐Ming (Angewandte Chemie International Edition, 2019)
The essence of rational design syntheses of functional inorganic materials lies in understanding and control of crystal structures that determine the physical properties. AgGaS2 has the highest figure of merit for IR nonlinear optical interactions to date, but suffers low laser‐induced damage threshold (LIDT). The partial Li substitution of Ag atoms is now shown to push up the bottom of the conduction band and flatten the top of the valence band, leading to an ultrawide band gap of 3.40 eV (record high for AgGaS2, indicating a transparency edging nearly 180 nm shorter than that of AgGaS2), which gives Li0.60Ag0.40GaS2 a LIDT 8.6 times stronger when AgGaS2 is compared. Li0.60Ag0.40GaS2 exhibits 1.1 times stronger nonlinear susceptibility, which is because the energy‐favorable Li substitution gradually decreases the sulfur dislocation in the lattice, which allows a better geometric superposition of nonlinear optical tensors. Lithium substitution maintains the symmetry of AgGaS2 structure and leads to an ultrawide band gap, simultaneously enhanced laser induced damage threshold (LIDT), and large second harmonic generation (SHG) that are otherwise inversely correlated. These enhancements are governed by the energy‐favorable decrease in dislocation in the lattice.